Management of Femoral Bone Defect after Gunshot Injury using Circular External Fixator (Journal of Pakistan Orthopaedic Association, 2018)
Objectives: Retrospective evaluation of healing index (HI) and consolidation time (CT) of gunshot femoral bone loss managed using conventional Ilizarov frame (CIF) versus Talyar Spatial Frame (TSF) fixator.Methods: This multicenter study included 15 patients had gunshot femoral bone loss of about 6 cm and average soft tissue defects of about 7 cm. External fixator was used in 9 patients, soft tissue defect was directly closed in 5 patients, using rotational flap in 5 patients, multiple Z-plasty in 2 patients and in 3 patients soft tissue defect was open managed and closed by secondary intention after application of CIF fixator. CIF fixator was used in 8 and TSF fixator in 7 patients. Mean latency period before starting distraction osteogenesis was 12.8±0.8; range: 12-14 days.Results: Mean distraction rate was 1.2±0.3 mm/day and inter-fragmentary compression rate was 0.25 mm/day for 5-7 days. Mean consolidation time was 97.8±18.1 days, and all patients had bone lengthening for a mean of 6.4±1.2 with a mean healing index of 15.3±1.37; range: 13.2-17.3. Patients categorized according to type of fixator showed non-significant (p>0.05) difference as regards clinical data.Conclusion: Distraction osteogenesis for gunshot femoral bone injuries could be achieved successfully using either Ilizarov or TSF circular fixator. Both fixators allowed bone lengthening within reasonable CT and with HI of about 15 days/cm.